Hypertension moderates the relationship between plasma beta-amyloid and cognitive impairment: a cross-sectional study in Xi’an, China - Ziyu Liu; Yaoli He; Simeng Cui; Liangjun Dang; Binyan Zhang; Jin Wang; Wenhui Lu; Kang Huo; Yu Jiang; Chen Chen; Ling Gao; Shan Wei; et al. (Frontiers in Aging Neuroscience)
BackgroundPlasma beta-amyloid (Aβ) are important biomarkers for Alzheimer’s disease and cognitive impairment (CI), but results are controversial. It remains unclear whether hypertension modulates their relationship. This cross-sectional study investigates whether hypertension moderates the relationship between plasma Aβ and cognitive impairment (CI).MethodsThis cross-sectional study included 1488 subjects ≥ 40 years from rural areas of northwestern China. CI was defined as a Mini-Mental State Examination score lower than the cutoff. Firstly, plasma Aβ40, Aβ42, Aβ42/Aβ40 were analyzed as restricted cubic spline. Then, categories of combined plasma Aβ were created by making bisection of plasma Aβ according to average and combining them as L-Aβ40 and L-Aβ42, H-Aβ40 and L-Aβ42, L-Aβ40 and H-Aβ42, H-Aβ40 and H-Aβ42. Decreased plasma Aβ40 was defined as < 25th percentile. Multivariate logistic regression examined the relationship between plasma Aβ and CI in total population, the hypertension subgroup and the non-hypertension subgroup.Results737 participants (49.5%) had hypertension and 189 participants (12.7%) had CI. Simultaneously elevated plasma Aβ40 and Aβ42 was associated with CI in hypertension (H-Aβ40 and H-Aβ42 vs. L-Aβ40 and L-Aβ42, 21.1% vs.10.7%, P = 0.033; OR = 1.984 [95% CI, 1.067–3.691], P = 0.030) but not in the non-hypertension. Decreased plasma Aβ40 was associated with CI in the non-hypertension (14.9% vs. 9.2%, P = 0.026; OR = 1.728 [95% CI, 1.018–2.931], P = 0.043) but not in the hypertension.ConclusionHypertension is an important modulator in the relationship between plasma Aβ and CI. Simultaneously elevated plasma Aβ40 and Aβ42 in the hypertension, and decreased plasma Aβ40 in the non-hypertension, may be risk factors for CI. These findings emphasize the need to consider hypertension in CI detection.